United Nations - Bailey, Sydney D. author. aut Link
VII, 129 p.
Keywords: A beginner's guide to the United Nations which sets out the purposes and structure of this organization and also discusses how much power the UN really has and whether the need for and the role of the UN in the world is justified. Six contemporary criticisms of the UN are also analyzed.